Understanding public policy : theories and issues - Cairney, Paul, 1973- (London Red Globe press, 2020)
"This book is a new introduction to theories of public policy. The author provides an accessible assessment of a wide range of theories and models from policy cycles, policy transfer, rational choice and socio-economic explanations to multi-level governance, advocacy coalitions and punctuated equilibrium and of their value to policy analysis"--Provided by publisher.
Machine generated contents note: -- Introduction: A Multiple Lens Approach to Policy Change -- What is Public Policy and How Do We Identify Continuity and Change? -- Power, Governance and Decision-Making -- Institutions and Policy Change -- Rationality and Incrementalism -- Structural explanations -- Rational Choice theory -- Multi-level Governance -- Punctuated Equilibrium and Venue Shift -- Advocacy Coalition Framework -- The Role of Ideas, Knowledge and Beliefs -- Policy Transfer -- Implementation, Evaluation and Learning -- Conclusion.
Includes bibliographical references and index.
Keywords: Political planning; Public administration